2021
DOI: 10.32598/hms.27.3.3213.1
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Bacteruria and Its Relationship With ABO Blood Group in Pregnant Women

Abstract: Aims: Blood Group Antigens (ABO) are present on the surface of all cells, including urinary tract cells. Besides, they are a predisposing factor for infection in various parts of the body. The present study aimed to determine the prevalence of bacteriuria and its relationship with different blood groups. Methods & Materials: This descriptive-analytical (cross-sectional) study was performed in 2019 on 400 pregnant women who were selected by convenience sampling method. For each pregnant woman referring to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Benli et al (2019) noticed the association between lower urinary tract infection and blood group A. Another study indicated that O blood groups in pregnant women were more frequent than B blood groups with urinary infec-tions (Mahmoudian et al, 2021). The present study is important and different from other research because Pantoea spp.…”
Section: Virulence Detection and Distribution Of Pantoea Spcontrasting
confidence: 55%
“…Benli et al (2019) noticed the association between lower urinary tract infection and blood group A. Another study indicated that O blood groups in pregnant women were more frequent than B blood groups with urinary infec-tions (Mahmoudian et al, 2021). The present study is important and different from other research because Pantoea spp.…”
Section: Virulence Detection and Distribution Of Pantoea Spcontrasting
confidence: 55%